Determinants and consequences of the unification of dual-class shares - Anete Pajuste (European Central Bank (ECB), 2005)
This paper explores the reasons why an increasing number of firms in continental Europe are unifying their shares into a single class, and analyzes the consequences of this restructuring. Interestingly, recent changes in corporate governance environment have created a situation when the reasons that once caused the introduction of dual-class shares, i.e., the need to issue new equity and to defend firm from a possible takeover, are the same that now motivate firms to switch back to one share-one vote. Meanwhile, higher value of control rights (e.g., high separation between control and cash flow rights) significantly reduces the likelihood of unification. Finally, the data show that firm value increases after the unification.
Keywords: G32; G34; 330; Corporate governance; dual-class shares; one share-one vote; Corporate Governance; Aktie; Deutschland; Vorzugsaktie